Interchange and value creation: competitive possibilities derived from network strategy (Revista de Administração, 2012)
The sharing of costs and of knowledge, reflected in this paper as interchange and creation of value, was studied in two corporate food retail networks in the central area of Rio Grande do Sul state. The objective was to investigate whether the competitive possibilities that are due to a network strategy are being exploited by the managers of the associated companies. The research was conducted using the case study method, for which the data was collected through in loco visits involving interviews with the main executives of the networks and questionnaires for the managers of the associated companies. The results indicate that both groups explore with greater emphasis the possibilities of value interchange, especially in the joint relations of acquisition and customer relations, to the detriment of the other components of the value network. On the other hand, in terms of creating value, the research found that there is a strong learning environment in both networks. However, difficulties hindered the actual creation of value through deliberate actions.